Treatment of steroid-resistant pediatric nephrotic syndrome - Hee Gyung Kang (Korean Pediatric Society, 2011)
Children who suffer from steroid-resistant nephrotic syndrome (SRNS) require aggressive treatment to achieve remission. When intravenous high-dose methylprednisolone fails, calcineurin inhibitors, such as cyclosporine and tacrolimus, are used as the first line of treatment. A significant number of patients with SRNS progress to end-stage renal disease if remission is not achieved. For these children, renal replacement therapy can also be problematic; peritoneal dialysis may be accompanied by significant protein loss through the peritoneal membrane, and kidney allograft transplantation may be complicated by recurrence of SRNS. Plasmapheresis and rituximab were initially used for treatment of recurrent SRNS after transplantation; these are now under consideration as rescue therapies for refractory SRNS. Although the prognosis of SRNS is complicated and unfavorable, intensive treatment in the early stages of the disease may achieve remission in more than half of the patients. Therefore, timely referral of pediatric SRNS patients to pediatric nephrology specialists for histological and genetic diagnosis and treatment is highly recommended.